Research progress on hepatitis E virus and blood safety - Miao LIU (Zhongguo shuxue zazhi, 2023)
Hepatitis E virus (HEV) is one of the main reasons of acute viral hepatitis. Although the majority of hepatitis E virus infection in humans is transmitted by fecal-oral route around the world, transfusion-transmitted HEV (TT-HEV) has attracted more and more attention as an emerging global health problem. Worldwide, 0.001 3%-0.281 0% of blood donors are HEV virus asymptomatic infection, and 0.27%-60.50% of blood donors have anti-HEV immunoglobulin antibody IgG. Blood recipient could get infected with HEV even if viral load in the blood is extremely low, which poses a great threat to blood safety. Therefore, HEV screening in blood donors has become an important concern in many countries. This article reviews the evidence and typical cases of TT-HEV, as well as the detection protocols and results of HEV screening in different countries, in order to provide evidence for whether HEV screening should be included in routine screening items for voluntary blood donors in China.